Application of Major and Trace Elements for Detecting the Origin of Groundwater: Lithium Enrichment in Ain Al-Harrah Hot Spring Influenced by Red Sea, Saudi Arabia - Rofiqul Umam; Korhan Cengiz; Ahmad Said (CV FOUNDAE, 2024)
Major and trace elements are valuable tracers for understanding the groundwater cycle. In groundwater flow path applications, these elements help delineate groundwater flow paths and identify areas of recharge and discharge. While in geothermal systems, the major and trace elements can indicate the contribution of deep hydrothermal fluids. In this study, we used major and trace elements as a groundwater tracer used to determine the origin of the Ain Al-Harrah hot spring in Saudi Arabia. Water sample data collection was taken from previous studies. In the data collection process, pre-washed 0.5 L polyethylene bottles were used to collect a total of five water samples from Ain Al-Harrah hot spring, Saudi Arabia. To prevent contamination, all samples were stored in a refrigerated room to maintain their chemical composition until the analysis process. The analytical results of the study showed that most of the hot water samples from Ain Al-Harrah hot spring, Saudi Arabia had been influenced by seawater which exceeded the limit value of x = 0.86 in the Na/Cl ratio. In addition, the value of y = 0.1 at the SO4/Cl ratio is the horizontal limit between the two. The interpretation of Cl against Cl/Li also confirms that the hot springs of Ain Al-Harrah, Saudi Arabia have been largely mixed with surface water. In addition, it is likely that the origin of the hot springs of Ain Al-Harrah, Saudi Arabia is also from seawater intrusion from red sea that has undergone mixing by meteoric water.